Analisis Pola Komunikasi Pada Penggunaan Fitur Polling Whatssapp Sebagai Media Voting Digital - Alfi, Alfiana Yuniar Rahmawati; Widiyoko, Chandra Arie (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2025)
This study discusses changes in communication patterns in the 'Aisyiyah Sampung organization group as an impact of the use of the polling feature on the WhatsApp application as a digital voting medium. The presence of digital technology allows polling activities to no longer be limited to the political realm, but also play an active role in the decision-making process in various activities. The purpose of this study is to determine the use of the WhatsApp polling feature in the context of group communication of the 'Aisyiyah organization and to analyze the communication patterns formed during the digital voting process. This study uses a qualitative approach with a case study method. Data were obtained through non-participatory observation, digital documentation, and in-depth interviews with selected informants from members of the 'Aisyiyah organization who were directly involved in the digital voting process. Data were analyzed using symbolic interaction analysis techniques to reveal the meaning and communication patterns formed. The results of the study show that the use of the 'Aisyiyah organization's WhatsApp polling feature in digital voting deliberations can create a structured, efficient, practical, and minimally conflicted communication pattern compared to open discussions. The use of this polling feature shows a collaborative communication model where each group member has an active role in voting. This creates a sense of collective involvement and responsibility, resulting in more effective decisions.